The dose-dependent effect of chronic Verapamil treatment on cardiac function in isolated rat heart with Hypertension. (24th May 2021) - Simovic, S; Jeremic, J; Davidovic, G; Srejovic, I; Zivkovic, V; Ravic, M; Nikolic, M; Iric-Cupic, V; Vucic, R; Sreckovic, M; Miloradovic, V; Andjic, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Verapamil, a calcium channel blocker, is used for treatment of hypertension, paroxysmal supraventricular tachycardia  and angina pectoris. It primarily blocks L-type calcium channels preventing excessive influx of calcium into cardiomyocytes, leading to negative inotropic effect, and smooth muscle cells resulting in reduced relaxation of vasculature. With calcium antagonism it also causes negative chronotropic effect. However, there is no data on it's dose-dependent effects on cardiac dynamic parameters and heart rate on isolated rat heart with hypertension. Purpose: To investigate chronic, dose-dependent effects of Verapamil on cardiodynamic parameters in isolated rat heart with hypertension. Methods: The present 4-week study was carried out on 24 spontaneously hypertensive Wistar Kyoto male rats  (6 weeks old): Control (n = 6), rats treated with 0.5 mg/kg/day of Verapamil (n = 6), rats treated with 5 mg/kg/day of Verapamil (n = 6) and rats treated with 50 mg/kg/day of Verapamil (n = 6). Isolated rat hearts were perfused on Langendorff perfusion apparatus. Results: Chronic, low-dose Verapamil treatment significantly depressed function of all cardiodynamic parameters of the hypertensive heart when compared to the rats treated with higher doses of Verapamil (p < 0.001), except on the coronary flow and heart rate when compared to the Control (p= 0.137; p = 1.000, respectively). There was no significant differences between Verapamil in middle dose (5 mg/kg/day) and the Control group in inotropic (p = 0.415) and lusitropic (p = 1.000) effects, while it significantly lowered values of coronary flow (p = 0.002). It achieved significantly lower inotropic, lusitropic and chronotropic effects (p < 0.001) than high Verapamil dose and significantly better inotropic (p = 0.017), lusitropic (p < 0.001), but not chronotropic effects than low-dose Verapamil treatment (p = 0.179). High-dose, chronic treatment with Verapamil significantly intensified function of  the isolated rat heart with hypertension when compared to Control and lower doses of Verapamil (p < 0.001), without significant effects on coronary flow (p = 0.363). Conclusions: Chronic treatment with Verapamil in high dose achieved better inotropic, chronotropic and lusitropic effects than treatment in low and middle doses of Verapamil, without significant effects on coronary flow. There is dose-depended effect of chronic Verapamil treatment on cardiac function of isolated rat heart with hypertension.